Influence of hydrocarbon environment on electrical characteristics of Ge-As-Se-S chalcogenide glass system (JOURNAL OF ADVANCES IN PHYSICS, 2024)
The effect of propane-butane gas mixture on volt-Ampere characteristic (VAX) of thin–layer sandwich structure Al-Ge33As17S35Se15-Te obtained by thermal evaporation method in vacuum was investigated. It has been established that under the influence of gas atoms, the oscillations observed in VAX gradually decrease and disappear. This result is explained by the accumulation of neutral gas atoms into lower atomar pores. It has been shown that neutral gas atoms collected in pores lead to weakening of thermal-field ionization processes of U--centers, and to increase the speed of periodic deflection of charge carriers by these centers, which leads to an increase in the resistance of the sample.